DEVELOPMENT OF DIGITAL RIGHTS IN UKRAINE - Yamnenko, Tetiana; Misko, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: determination of trends in the development of human rights in the digital sphere in Ukraine and ways of their actualization. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: the research and analysis of scientific and theoretical definitions of the concept of digital human rights, the definition of the legal regulation of relations arising in the digital sphere in our country and its relevance, the comparison of the status of legal regulation of digital human rights in Ukraine with the experience of the European Union. Discussion: the possibilities of applying different doctrinal approaches to digital human rights in Ukraine by analyzing the experience of the European Union, given the number of digital rights that require regulatory regulation. Some of them are fundamental in their importance for a person and require constitutionalization. Nowadays humanity faces the challenges that determine the development and usage of digital technologies not only in the familiar spheres. Digital technologies become more common for people in everyday life, relationships between people, education, etc. Such factors as the spread of the COVID-19 pandemic or the start of a full-scale war in Ukraine have affected the usage of the latest technologies for receiving urgent documents, the ability to work or study remotely, etc. All these presuppose the actualization of the topic of the development and use by individuals of their digital rights, the implementation, as well as full-fledged legal regulation of these rights and their further research in the scientific community. According to today’s reality, it is important to emphasize that the digital transformation of the modern world is one of the most influential factors in the development of society and legal science as a result. That is why there is an urgent question about the need to highlight and define such a new category of human rights as digital rights at the legislative level.